Macroeconomic determinants of the interest rate term structure: A Svensson model analysis - Cristiane Benetti; José Monteiro Varanda Neto; Rogério Mori (Economies, 2025)
This study develops a model to predict and explain short-term fluctuations in the Brazilian local currency interest rate term structure. The model relies on the potential relationship between these movements and key macroeconomic factors. The methodology consists of two stages. First, the Svensson model is applied to fit the daily yield curve data. This involves maximizing the R2 statistic in an OLS regression, following the Nelson-Siegel approach. The median decay parameters are then fixed for subsequent estimations. In the second stage, with the daily yield curve estimates in hand, another OLS regression is conducted. This regression incorporates the idea that Svensson's betas are influenced by macroeconomic variables.
Keywords: C53; C58; G17; 330; term structure of interest rates; Svensson model; Nelson-Siegel model; parametric models; macroeconomic variables; trading algorithms